Gasification of Pelletized Corn Residues with Oxygen Enriched Air and Steam - Sittisun, Poramate; Tippayawong, Nakorn; Shimpalee, Sirivatch (Center of Biomass & Renewable Energy, Diponegoro University, 2019)
This work studied generation of producer gas using oxygen-enriched air and steam mixture as gasifying medium. Corn residues consisting of cobs and stover were used as biomass feedstock. Both corn residues were pelletized and gasified separately with normal air, oxygen enriched air and steam mixture in a fixed bed reactor. Effects of oxygen concentration in enriched air (21-50%), equivalence ratio (0.15-0.35), and steam to biomass ratio (0-0.8) on the yield of product gas, the combustible gas composition such as H2, CO, and CH4, the lower heating value (LHV), and the gasification efficiency were investigated. It was found that the decrease in nitrogen dilution in oxygen enriched air increased proportion of combustible gas components, improved the LHV of producer gas, but gasification efficiency was not affected. The increase in equivalence ratio favoured high product gas yield but decreased combustible gas components and LHV. It was also observed that introduction of steam enhanced H2 production but excessive steam degraded fuel gas quality and decreased gasification efficiency. The highest gasification efficiency of each oxygen concentration was at equivalence ratio of 0.3 and steam to biomass ratio of 0.58 for cob, and 0.22 and 0.68 for stover, respectively. Â©2019. CBIORE-IJRED. All rights reserved